2020
DOI: 10.1126/sciadv.aba4526
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal extracellular matrix hydrogel mitigates metaplastic change in a dog model of Barrett’s esophagus

Abstract: Chronic inflammatory gastric reflux alters the esophageal microenvironment and induces metaplastic transformation of the epithelium, a precancerous condition termed Barrett’s esophagus (BE). The microenvironmental niche, which includes the extracellular matrix (ECM), substantially influences cell phenotype. ECM harvested from normal porcine esophageal mucosa (eECM) was formulated as a mucoadhesive hydrogel, and shown to largely retain basement membrane and matrix-cell adhesion proteins. Dogs with BE we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 59 publications
1
21
0
Order By: Relevance
“…Several protein species (COL5A1, COL5A2, FBLN5, TGFBI, TINAGL1) were enriched in the saline-solubilization process. The results support the findings of other ECM-based studies and the TOFT; that is, that non-neoplastic mammalian ECM contains bioactive cues that can antagonize cancer cells and their in vivo progression [ 10 14 , 16 ]. The findings were present in vitro in both primary glioma cells and glioma cell lines, though with differing sensitivities.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Several protein species (COL5A1, COL5A2, FBLN5, TGFBI, TINAGL1) were enriched in the saline-solubilization process. The results support the findings of other ECM-based studies and the TOFT; that is, that non-neoplastic mammalian ECM contains bioactive cues that can antagonize cancer cells and their in vivo progression [ 10 14 , 16 ]. The findings were present in vitro in both primary glioma cells and glioma cell lines, though with differing sensitivities.…”
Section: Discussionsupporting
confidence: 88%
“…A recent study showed the beneficial therapeutic effects of an ECM hydrogel derived from normal esophageal tissues upon dysplastic esophageal mucosa (i.e. Barrett’s esophagus) in which metaplastic cells regressed to a squamous epithelial phenotype in a canine model [ 16 ]. Importantly, a study by the same group found increased apoptosis in one metaplastic and two neoplastic cell lines exposed to urinary ladder matrix ECM [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Older studies modeling metaplasia in the canine showed a more anatomically correct emergence in response to surgically induced reflux. 7 , 186 , 187 These models support the emergence of supposed BE stem cells from the GEJ and obviously are useful for the investigation of inflammatory contributors; however, antibodies and other tools are currently of limited availability for canine and porcine models, and none thus far have been investigated for mutational burden, a critical component of the inherent oncogenic potential of BE. A quicker route to fundamental, human, relevant, and translational discoveries may be garnered from the use of recent organoid technologies capable of mirroring BE and EAC pathologies ex vivo.…”
Section: Final Thoughts and Future Directionsmentioning
confidence: 99%
“…For instance, engineered low-pathogenic microbes have been recently shown to promote mesenchymal stem cells reprogramming into multiple lineages by modulating CSK architecture (Sivasubramaniam and Franks, 2016). Even more intriguing are results provided by Badylak's group (Naranjo et al, 2020), which demonstrated that pre-neoplastic lesions and inflammation in Barrett's esophagus can be mitigated, and the metaplastic changes can be reversed when the microenvironment is "reverted" into a more normal, homeostatic state by coating the esophageal mucosa with a mucoadhesive hydrogel composed of normal porcine esophageal extra cellular matrix components. Recognizing how to modulate the CSK by manipulating/engineering the microenvironment (Ingber, 2008) could help in planning new pharmacological approaches in those diseases arising as a result of disrupted crosstalk between cells and their microenvironment, including developmental-related defects, cancer, and inflammation-based diseases.…”
Section: The Impact Of the Novel Paradigmmentioning
confidence: 99%